Empirical Analysis of Factors Influencing Use of Internet on Ships - A. S. Saravanan; Jayalakshmy Ramachandran; A. Seetharaman; Karripur Nanda Kumar; Kailash C. Joshi (Journal of Accounting, Business and Management (JABM), 2018)
The purpose of this study was to evaluate the factors influencing the emergence of internet on ships and the resultant cost. Data collected from 255 respondents, mainly seafarers (captain and officers) and shore- based ship managers revealed that emergence of the internet on ships is influenced by perceived usefulness, organisation readiness, external pressure and technology penetration. It is also witnessed that cost of internet on ships has an effect on the penetration of the internet and new technology. The emergence of the internet on ships provides an effective communication link with all stakeholders of the ship, enhances safety and security with real time data on cargo, incidents, piracy, terrorism and weather conditions. It facilitates timely delivery of stores and spare parts for ship repairs and maintenance, thus providing immense satisfaction to all stakeholders. It thus has a significant impact on the industry.